A General Approach on Surfactants Use and Properties in Drug Delivery Systems - de Freitas Araújo Reis, Mysrayn Y.; de Araújo Régo, Renaly I.; Rocha, Beatriz P.; Guedes, Gabryella G.; de Medeiros Ramalho, Ízola M.; de Medeiros Cavalcanti, Airlla L.; Guimarães, Geovani P.; de Lima Damasceno, Bolívar P.G. (Current Pharmaceutical Design, 2021)
Surfactants are amphiphilic molecules of great interest in the pharmaceutical field which are used in combination with other adjuvants to solubilize poorly soluble drugs, improve their dissolution profile, promote permeation, improve drug delivery, enhance stabilization, among other characteristics. Literature shows that surfactants are included in several pharmaceutical compositions: tablets, solid dispersions, emulsions, microemulsions, nanoemulsions, liposomes and niosomes. This review aims to elucidate the different classes of surfactants based on their charges (cationic, anionic, nonionic, zwitterionic, and dimeric), the micelles formation process, and how surfactant molecules geometry can affect this phenomenon. Moreover, current studies regarding the benefits of surfactants in the development of formulations are presented. Finally, a discussion on how charges and chain length of surfactants can affect the stratum corneum epithelial cells leading to increased permeation or skin irritability is reported.
Keywords: micelles